Analisis Preservasi Arsip Sebagai Upaya Pelestarian Memori Kolektif Bangsa: Studi Media Sosial - Azzahra, Sharon Luna; Lubis, Salsabila Madogan; Wardi, Puja Ayu; Putri, Zaskia Mardiyani; Azzahra, Reisa Dinda; Kestadireja, Khansa Tiarazzalfaa; Zahrani, Valiza Nur; Dewi, Via Risti (Prisani Cendekia, 2025)
In the context of the digital era, the widespread dissemination of educational content related to archival preservation necessitates critical analysis to evaluate the public's capacity to comprehend, accept, and apply such information. This study aims to assess public perceptions of archival preservation as a means to safeguard the nation's collective memory, based on responses to educational content about preservation disseminated via social media. The theory employed in this study is content analysis. The methodology of this study adopts a quantitative approach that analyzes data using four parameters: tone, narrative, competence, and image. It aims to collect and process data in an objective, valid, reliable, and replicable manner. Based on an analysis of social media comments, the average scores for each parameter were as follows: Tone (1.9), Narrative (1.6), Competence (2.3), and Imagery (2.0). The overall mean score across all parameters was 1.95, which falls into the